An industrial policy framework for OECD countries Old debates, new perspectives - Criscuolo, Chiara (OECD Publishing, 2022)
The debate on industrial policy has made a comeback in both academic and policy circles. Yet, no consensus exists on an industrial policy paradigm and the absence of a common reference framework unduly obfuscates the debate - even which interventions are to be considered "industrial policy" is not clear-cut. Against this background, this paper proposes a coherent framework for analysing the formulation of industrial policy, relying on a purposefully broad definition of the latter. Leveraging the proposed framework and a companion paper which synthetises the available empirical evidence, this paper stresses the complementarities between policy instruments, thereby justifying the use of industrial strategies, acknowledges the role of targeted industrial strategies, which can direct technological change and growth, and of demand-side instruments, which can contribute to transformative industrial change, but calls for a stronger emphasis on evaluation and the regular re-assessment of targeted industrial strategies
Keywords: Science and Technology